IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI MELALUI PBL UNTUK MENINGKATKAN KEMAMPUAN LITERASI SAINS SISWA KELAS X.3 SMAN RAMBIPUJI - Balkis Yuliar Tilamsari; Sawitri Komarayanti; Sri Purwaningsih (Program Studi Pendidikan IPA FKIP Universitas Jember, 2023)
Literacy skills are needed by students in the rapid development of information and communication technology, and the internet. The results of the latest PISA survey showed low students' reading ability when compared to the previous year. This study aims to improve the scientific literacy skills of class X.3 students of SMAN Rambipuji by applying differentiation learning through problem-based learning. The type of research used is the action research class which consists of the planning, implementation, observation and reflection stages. The subjects in this study were students of class X.3 at SMAN Rambipuji Jember which consisted of 36 students. Data were obtained from interviews, observations, documentation, and tests in the form of post-test questions which contained indicators of scientific literacy. The results showed that there was an increase in scientific literacy skills of X.3 class students from an average score of 54.6 to 70.3 when differentiated learning was applied through problem-based learning in cycle I and cycle II